2021
DOI: 10.3389/fcimb.2021.654745
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis and Septic Arthritis Due to Burkholderia pseudomallei: A 10-Year Retrospective Melioidosis Study From South China

Abstract: Burkholderia pseudomallei is the causative agent of melioidosis, endemic mainly in tropical and subtropical areas. Its clinical manifestation is broad ranging from a localized skin lesion to a life-threatening systemic disease. Osteomyelitis and septic arthritis caused by B. pseudomallei are a rare, fatal illness, whose clinical features have not been illustrated in mainland China. Over 10 years (2010 to 2019), of 334 culture-confirmed melioidosis in Hainan province, China, 44 patients (13.2%) were confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
8
1
Order By: Relevance
“…As persistent hyperglycaemia further worsens the condition of melioidosis, the aggravation of melioidosis also leads to poor blood sugar control, forming a vicious cycle [ 17 , 18 ]. Most of the cases in our study also occurred in coastal areas and during the rainy season in summer and fall, which is consistent with the case reports in Hainan, China [ 19 , 20 ]. In our study, we have observed a sharp increasing in the number of cases after 2014, reasons for which may be for the increased awareness of melioidosis, improvement of B. pseudomallei detection technology and higher level of diagnosis of melioidosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As persistent hyperglycaemia further worsens the condition of melioidosis, the aggravation of melioidosis also leads to poor blood sugar control, forming a vicious cycle [ 17 , 18 ]. Most of the cases in our study also occurred in coastal areas and during the rainy season in summer and fall, which is consistent with the case reports in Hainan, China [ 19 , 20 ]. In our study, we have observed a sharp increasing in the number of cases after 2014, reasons for which may be for the increased awareness of melioidosis, improvement of B. pseudomallei detection technology and higher level of diagnosis of melioidosis.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, six patients (6.67%) died of illness during hospitalisation, with a mortality rate lower than the 10–40% reported in previous studies [ 5 , 17 , 19 ]. This was related to the increasing awareness of melioidosis and to the poor follow-up after the automatic discharge of some patients with worsened disease in our study due to local cultural customs and economic reasons.…”
Section: Discussioncontrasting
confidence: 80%
“…A retrospective study done by Perumal et al 26 showed that out of 342 patients diagnosed with B. pseudomallei , 37 (9.2%) had musculoskeletal involvement. Knee joint is reported to be the most commonly involved joint by melioidosis, as opposed to the shoulder joint involvement in our case 27…”
Section: Discussionmentioning
confidence: 48%
“…Fever is the most common clinical presentation of melioidosis, in 66–95.5% of cases. 7 , 8 Melioidosis caused by B. pseudomallei can cause FUO, and should be included in the differential diagnosis of FUO, especially for patients with FUO who are from endemic regions.…”
Section: Discussionmentioning
confidence: 99%